The Effect of Cobalt Doping in Structural Phase Transition of SmFe1-xCoxAsO Measured by Low-temperature X-ray Diffraction - Khan, A.; Rahman, A.; Naher, S.; Kaneko, H.; Yun, Y.; Savinkov, A.; Suzuki, H.; Li, Y. K.; Tao, Q.; Cao, G. H.; et al. (Journal of Scientific Research, 2012)
The parent compound SmFeAsO shows structural phase transition from tetragonal to orthorhombic at the temperature TD = 144 K. In the compound SmFe1-xCoxAsO, with increasing x the structural transition temperature TD and SDW TN decreases and reaches 0 K at the critical concentration xc. The X-ray diffraction technique has been used here to study the structural phase transition temperature. It is observed that the (400) peak of the parent compound SmFeAsO splits into two peaks (400) and (040), when the temperature is lower than the structural transition temperature TD. The structural phase transition of Co doped compounds SmFe1-xCoxAsO has also been studied for x = 0, 0.01, 0.025 and 0.075. The phase transition temperature TD for SmFe0.99Co0.01AsO, SmFe0.975Co0.025AsO and SmFe0.925Co0.075AsO are 134 K, 118 K and 4 K, respectively. The phase diagram of TD versus lattice spacing reveals that the structural transition temperature decreases with shrinking lattice constant along c-axis similar to the decrease of the structural phase transition temperature with increasing Co concentration. The phase diagrams of SmFe1-xCoxAsO and Sm(O1-xFx)FeAs show a similar nature. © 2012 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v4i3.10248 J. Sci. Res. 4 (3), 541-550 (2012)